Top heavy: beyond the Global North and the justification for global administrative law - Xavier, Sujith (Indian Journal of International Law, 2017)
Global administrative law scholars have argued that global administrative law’s principles and normativity can bring about legitimacy to global governance institutions, and subsequently benefit the people of the Global South. I challenge these recent arguments that suggest global administrative law has managed to incorporate the concerns of the Third World. I caution international lawyers’ attempts to theorize global governance as administration to fill the democracy gap within the global space. My arguments are premised on the history of domestic administrative law and its uses to facilitate the settler colonial project in places like North America. I first examine the two animating claims within global administrative law and then focus, based on taxonomies available within the current literature, on procedural administrative law. The procedural argument has been developed by American legal scholars who want to deploy their common law based notions of administrative law within the global space. Based on this analysis, I develop and deploy a case study from the International Criminal Tribunal for Rwanda as illustration of judicial review within an international criminal institution set up by the UN Security Council. In the final section, I challenge global administrative lawyers’ arguments that global administrative law can be a tool of emancipation for the people of the Global South based on the ICTR case study.
Keywords: Sujith Xavier